Media Democratization, Public Spaces and Cultural Diversity - Henrique Demarchi, Carlos [UNESP] (Univ Fundacao Mineira Educacao & Cultura-fumec, 2016)
This article aims to examine the possibilities for ensuring cultural diversity in the Brazilian commercial television system. It focuses on the discussion of constructing public spaces, taking the view that State intervention through the implementation of policies for the area may diversify the content aired by the broadcasters.
Keywords: Cultural Diversity; Media Democratization; Public Spaces